Keluhan pada Genetalia Eksternal Ditinjau dari Pengetahuan dan Personal Hygiene Pada Siswi SMA - Delvia, Siska (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2016)
Reproductive organs are very sensitive and require special care. Knowledge and good care is a decisive factor in maintaining reproductive health. This study aims to determine the relationship between knowledge and personal hygiene with grievance on the external genitalia of high school student. The method used is the analytic survey with cross sectional approach. The sample in this study amounted to 65 people by using purposive sampling technique. The data is processed using the data processing program. Chi Square test indicates the significant value of p value 0.006 to the variable knowledge with grievance on the external genitalia. In variable personal hygiene with grievance on the external genitalia obtained significant value of p value 0.007. It is suggested to the students that have grievance in the area of the external genitalia in order to immediately go to the clinic or hospital nearby to prevent the situation worse.Keywords: knowledge, personal hygiene, complaints on external genetalia